DESAIN SUSTAINABLE VALUE STREAM MAPPING UNTUK EVALUASI KINERJA KEBERLANJUTAN PERUSAHAAN OBAT - Muhammad Nashir Rasshif; Purnawan Adi Wicaksono; Sri Hartini (Industrial Engineering Online Journal, 2023)
AbstractTo realize sustainable manufacturing, a company must consider three pillars: economic, environmental and social. Sustainable Value Stream Mapping (Sus-VSM) is a visual tool to identify sources of waste in the production process in economic, environmental and social dimensions. This study aims to design Sus-VSM to analyze drug companies' economic, environmental and social performance—a case study in this study at PT X Department of Antibiotics. The indicators on the economic dimension studied are product quality, the environmental dimension indicators are material consumption and the social dimension indicators are worker health and worker satisfaction.Kata kunci: Lean manufacturing, Sustainable Value Stream Mapping (Sus-VSM), Perusahaan obat